1996
DOI: 10.1021/ma9507251
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Pure Diblocks and Binary Diblock Blends of Poly(ethylene)−Poly(ethylethylene)

Abstract: We have determined the phase behavior of a series of model poly(ethylene)−poly(ethylethylene) (PE−PEE) diblock copolymers with poly(ethylene) block volume fractions (f PE) ranging from 0.25 to 0.46. Four ordered microstructures make contact with the ODT:  spheres arranged on a body-centered cubic lattice (Im3̄m space group), cylinders packed on a hexagonal lattice, a bicontinuous structure of space group Ia3̄d, and lamellae. A fifth ordered phase, tentatively identified as hexagonally perforated layers (HPL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
261
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(286 citation statements)
references
References 34 publications
22
261
1
2
Order By: Relevance
“…In contrast to the work of Zhao et al (1996) and Buzza et al (2000) we did not observe the slope in the order of 1/2 for the diblock copolymer with the lamellar morphology. A possible explanation is the missing long-range order of the lamellar morphology for the block copolymers of this study.…”
Section: Master Curvescontrasting
confidence: 99%
“…In contrast to the work of Zhao et al (1996) and Buzza et al (2000) we did not observe the slope in the order of 1/2 for the diblock copolymer with the lamellar morphology. A possible explanation is the missing long-range order of the lamellar morphology for the block copolymers of this study.…”
Section: Master Curvescontrasting
confidence: 99%
“…In addition, two-component block copolymer blends were employed in order to examine samples with weight fractions between those of the neat polymers, a technique that has been described elsewhere. 46 Blend samples were prepared by codissolving the two components in cyclohexane at approximately 80°C, followed by precipitation in methanol and drying in vacuum at 200°C. In order to observe the higher-order SAXS peaks necessary for identification of the equilibrium mesophase structure (see below), many of the samples required extended annealing, which was performed for 2-35 days in evacuated and sealed ampules at 160 -200°C.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al reported that hexagonally perforated layers 29 are converted to {121} DG in thin films 22,30 in the OOT from hexagonally perforated lamellar (HPL) to DG structures, whereas this kind of orderly transition is not observed in shear-oriented bulk. 17 3D observations by TEM and 3D-TEM were carried out using a JEM-2200FS system (JEOL Co., Ltd., Japan) operating at 200 kV, details of which can be found elsewhere. 26 Adapted with permission from ref 13.…”
Section: D Structural Analysis Of Ootsmentioning
confidence: 99%